Does Pedagogy Vary with Class Size in Introductory Economics - Siegfried, John J.; Kennedy, Peter (American Economic Review, 1995)
The norming of the third edition of the Test of Understanding College Economics (TUCE III) has produced a valuable data set (Phillip Saunders, 1994). These data describe 93 introductory macro and 96 introductory microeconomics classes taught by 131 different instructors at 53 U.S. colleges and universities in 1989-1990. It is tempting to use this sample to investigate how class size influences learning. The nonexperimental nature of the data, however, raises the possibility of an endogeneity problem: department chairs may assign better teachers to larger classes, and those teachers, in turn, may attract even greater numbers of students. Teaching quality, therefore, may be higher in larger classes. Thus, the discovery from these data of any deleterious effect on learning from larger classes may be only a lower bound. The education literature, admirably surveyed by Wilbert J. McKeachie (1990), suggests that learning is not much affected by class size. One reason for this result may be that instructors do not adjust their teaching methods to class size. In this paper we use the TUCE III data to examine whether introductory economics instructors vary pedagogy with class size. I. The Role of Instructor Behavior